Deep Learning Workshop Based On Moral Messages In Mathematics Learning: Design, Implementation And Assessment For Junior High School Teachers In Sanggau District - Edy Yusmin; Revi Lestari Pasaribu; Ade Mirza; Dona Fitriawan; Nadya Febriani Meldi; Metia Novianti; Agus Winarji; Bistari; Dede Suratman (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
Mathematics education plays a crucial role in shaping critical thinking skills and the character of 21st-century students. However, mathematics learning at the junior high school level, particularly in Sanggau Regency, still faces challenges in implementing methods that promote in-depth understanding and application. One relevant approach to address this issue is moral-based Deep Learning, which emphasizes not only cognitive aspects but also affective aspects and character values. This Community Service (PKM) activity was conducted by lecturers from the Mathematics Education Study Program, Faculty of Teacher Training and Education, Tanjungpura University, with the aim of improving the competence of junior high school teachers in designing, implementing, and evaluating Deep Learning-based mathematics learning. The activity methods included workshops, mentoring, and practical training in developing learning tools that integrate moral values. The results of the activity showed an increase in teachers' understanding of the Deep Learning concept and their ability to develop meaningful, contextual, and character-based learning designs. This activity is expected to contribute to improving the quality of mathematics learning in Sanggau Regency and encourage the emergence of a generation of students who are intellectually intelligent and strong in morality.